Everyday crochet : the complete beginner's guide - Gilbank, June (DK Publishing, 2022)
"You've seen gorgeous crochet items online and in boutique shops, and you'd love to learn to create them yourself. Now's your chance! Packed with hundreds of inspirational color photos and easy-to-follow instructions, this fun guide teaches how to hook your way to a wonderful new skill."